Association of paternal MTHFR polymorphisms (C677T) with clinical outcomes in ICSI treatment - Wan, Yangyang; Liu, Wenjing; Xu, Bo; Jiang, Xiaohua; Hua, Juan (Frontiers in Endocrinology, 2022)
Purpose: This study aims to investigate the association between sperm MTHFR polymorphisms (C677T) and embryo development, pregnancy and neonatal outcomes in ICSI treatment. Methods: A total of 191 infertile men undergoing ICSI treatment at the Reproductive and Genetic Hospital, The First Affiliated Hospital of USTC, were recruited between January 2020 and June 2021. The MTHFR C677T polymorphism genotyping was evaluated in these male patients, and they were stratified into three groups according to genotyping results: Control (CC), heterozygote mutated (CT), and mutated homozygote (TT). In addition, we conducted a comparative analysis of embryo development, pregnancy, and neonatal outcomes among these three groups. Results: The embryo development (including, normal fertilization rate (80.14% vs. 83.06% vs. 85.10%; (p=0.37)), High-quality embryos rate (45.26% vs. 43.69% vs. 46.04%; (p=0.72)), blastocyst formation rate (42.47% vs. 43.18% vs.39.38%; (p=0.62)), implantation rate (42.47% vs. 36.25% vs. 41.22%; (p=0.62)) and clinical pregnancy rate (64.71% vs. 58.75% vs. 66.67%; (p=0.59)) were comparable between these three groups. Moreover, no significant difference was observed in terms of pregnancy outcome (including, miscarriage rate (24.24% vs. 12.77% vs. 22.5%; (p=0.35)), and live birth rates (49.02% vs. 51.25% vs. 51.66%; (p=0.96))). Additionally, no marked difference was observed in terms of neonatal outcome (including, preterm delivery rate (24% vs. 14.63% vs. 9.67%; (p=0.35)), birth height (p=0.75), birth weight (p=0.3478), neonatal sex (p=0.48), gestational age at delivery (p=0.24), Apgar score (p=0.34), and birth defects (0% vs. 2% vs. 9%; (p=0.23)) between the study groups. Conclusion: The paternal MTHFR C677T polymorphism is not associated with embryo quality, pregnancy and neonatal outcomes in ICSI treatment. We, therefore, in our population MTHFR genotypes are not informative in explaining ICSI failure.